Erector Spinae Plane Block is Equivalent to Tumescent Local Anesthesia for Perioperative Pain Control with Abdominal Harvest for Fat Grafting - Shawhin Shahriari, MD; Avra Laarakker, MD; Donald Luna, MD; Kanwal Merchant, MD; Elizabeth Baker, MD; Mary Billstrand, MD; Jeffrey Wu, MD (Plastic and Reconstructive Surgery, Global Open, 2022)
Background:. There is increasing evidence that lidocaine is toxic to adipocytes and their precursors, which can contribute to the variability in fat graft resorption. Erector spinae plane (ESP) block is a new technique to provide analgesia of the trunk and would avoid lidocaine at the fat graft donor site. The aim of this study was to compare the efficacy of ESP block versus tumescent local anesthesia (TLA). Methods:. A retrospective review was performed for all patients who underwent autologous fat grafting from the abdomen at the University of New Mexico Hospital between February 2016 and March 2019. These patients received either ESP block or TLA during abdominal fat harvest. The primary endpoints were intraoperative, postoperative, and total morphine equivalents. Results:. There was no difference in the mean intraoperative, postoperative, and total morphine equivalents administered between the ESP and TLA groups. Conclusions:. ESP block is equivalent to TLA for analgesia when using an abdominal donor site for fat harvest. ESP block should be considered in fat-grafting cases to avoid the potential toxicity of lidocaine to the viability of adipocytes and preadipocytes.